2021
DOI: 10.1021/acs.jproteome.0c00973
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biological Mechanisms of Eucommiae Folium in Hypertensive Kidney Injury by Integration of Untargeted Metabolomics and Network Pharmacology

Abstract: Hypertensive kidney injury (Hki) is one of the most common complications of hypertension. Early prevention and treatment of renal injury in patients with hypertension is great significance. The study, which used an integrated ultraperformance liquid chromatography-tandem mass spectrometry (UPLC-MS) analysis, network pharmacology approach, and plasma metabolomics, aimed to discover the active ingredients and therapeutic mechanisms of Eucommiae folium (Ef) in treating Hki. The chemical components of Ef were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…The maps of 24 MFEU active components were drawn by ChemBioDraw Ultra 12.0 software. In this paper, the targets of ingredients with MFEU were found on the SwissTargetPrediction website (http://www.swisstargetprediction.ch/) [13]. All targets were deleted duplicate and false positive by SwissTargetPrediction website; 24 active ingredients and 255 targets were obtained after integration; 988 targets of fatigue, anti‐fatigue were retrieved and integrated from GeneCard, OMIM database.…”
Section: Resultsmentioning
confidence: 99%
“…The maps of 24 MFEU active components were drawn by ChemBioDraw Ultra 12.0 software. In this paper, the targets of ingredients with MFEU were found on the SwissTargetPrediction website (http://www.swisstargetprediction.ch/) [13]. All targets were deleted duplicate and false positive by SwissTargetPrediction website; 24 active ingredients and 255 targets were obtained after integration; 988 targets of fatigue, anti‐fatigue were retrieved and integrated from GeneCard, OMIM database.…”
Section: Resultsmentioning
confidence: 99%
“…Mangiferin, isomangiferin and neomangiferin as anti-inflammatory components could inhibit AA metabolism. An integrated UPLC/MS metabolomics was used to discover bioactive ingredients of Eucommiae folium (Ef) in treating kidney injury [144]. The results indicated that Ef could regulate the vascular endothelial growth factor, hypoxia-inducible factor 1, and glycerophospholipid pathways.…”
Section: Efficacy Evaluation Of Herbal Medicine and Natural Productsmentioning
confidence: 99%
“…Network toxicology can clarify the relationships between chemicals and the human body by considering the broader context of a biological network, which can elucidate the mechanism underlying adverse reactions of chemicals and highlight the complex regulation of signal pathways across multiple channels [ 20 ]. The metabolomics and network toxicology method could improve the accuracy and effectiveness [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%